Food Security in Cape Verde: objectives of public policies and results achieved - Simões, Elsa Barbosa (2019)
Through guided interviews with experts from the public sector, NGOs and international development aidagencies with experience in the implementation of public policies, this article makes a comparative analysisbetween practice and theory in the implementation of public policies for security food in Cape Verde. It isconcluded that social welfare policies are not entirely safeguarded and that to give this answer there is a pressing need to have an effective sustainable development policy for agriculture, improving the focus on quality of life and in fair economic and social policies and environmentally sustainable. Although there are no legal impediments for the organization of associations, there are also no mechanisms that promote participation in the development process.